EFISIENSI ISOLASI MINYAK ATSIRI DARI KULIT JERUK DENGAN METODE DESTILASI AIR-UAP DITINJAU DARI PERBANDINGAN BAHAN BAKU DAN PELARUT YANG DIGUNAKAN - Cahyati, Suci; Kurniasih, Yeti; Khery, Yusran (Hydrogen: Jurnal Kependidikan Kimia, 2016)
Citrus nobilis L. peel was used as a source of essential oil production through water-stem distillation method. The aim of this research was to compare yield and quality of essential oil from Citrus nobilis L. peel obtained from ratio of 0,2; 0,4 and 0,6 of raw material mass and solvent volume during water-stem distillation. In each run, 1000 mL of water was applied as solvent, and the distillation was performed for 6 hours.. Results show that the best yield and quality of the produced essential oil was obtained on 400 gram/1000 mL ratio. This ratio produced essential oil in a yield of 2.18 %, 0.8484 gram/ mL density, yellowish oil with orange typical aroma, and viscous. GC-MS analysis results of the oil show the composition of Limonene 56,96%, α-Pinene 3,86%, β-Phellandrene 1,02%, β-Pinene 2,40%, β-Myrcene 2,76%, Linalool 7,69%, 3-Cyclohexene-1-methanol 2,04%, Nerol 1,44% and Benzenedicarboxylic acid 14,50%.